PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH TERHADAP MOTIVASI KINERJA GURU - Nur, Alifianty; Nadia, Tita; Pustakawati, Anjani; Firdausy, Aulia (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2020)
The principal has a very important position so that the principal is required to have the ability and readiness to influence, encourage, invite to guide, move, direct and then do something that can help achieve the goals set. As an educational leader the principal has heavy responsibilities. The principal as a leader must be responsible for teacher upgrading. Therefore, this school has a special leadership style. The purpose of this research is to learn about the principal's leadership style and types, understanding motivation, motivational factors, understanding teacher performance, factors that improve performance and teacher performance standards. The method used in this study is the library method. Then the techniques of collecting data conduct library research, such as reading, writing, citing material related to the problem in approving this. The results of this study indicate that Theoretically, a significant positive impact of leadership style on teacher performance has a strong influence on the progress of the organization, especially educational institutions.